Symphysio Fundal Height (SFH) Measurement as a Predictor of Birth Weight (Faridpur Medical College Journal, 2013)
Fetal weight is a very important factor to make a decision about labor and delivery. Assuming that in large fetuses, dystocia and other complications like cerebral edema, neurological damage, hypoxia and asphyxia may result during or after the delivery. On the other hand, one of the causes of high perinatal mortality in our country is high rate of low birth weight. Rural people may not have access to ultrasonography which is one of the methods to predict birth weight. For these people alternative easy method is necessary. So we can assess fetal birth weight by measuring symphysio-fundal height. Total 100 consecutive pregnant women of gestational age more than 32 weeks admitted for delivery in the Obstetric and Gynaecology department of Faridpur General Hospital were the subject of this study. After selection of cases, a thorough clinical history was taken and elaborate physical examination was done. Common criteria for collection of data were followed in every case. The fetal weight estimated by Johnson's formula was recorded in the predesigned data sheet and then was compared with birth weight following delivery of the fetus. Collected data were compiled and relevant statistical calculations were done using computer based software. Statistical tests (Correlation) were done between actual birth weight (taken as dependant variable) and fetal weight (found by Johnson's Formula), symphysio fundal height (SFH), pre-delivery weight and height of the patients (taken as independent variables) and the tests revealed that actual birth weight was significantly correlated with fetal weight (found by Johnson's Formula), SFH, pre-delivery weight and height of the patients. Among these fetal weight and SFH had shown highest correlation. Regression analysis showed that SFH, maternal height and maternal weight explained respectively 59%, .011% and .009% of observed variation of birth weight. DOI: http://dx.doi.org/10.3329/fmcj.v7i2.13498 Faridpur Med. Coll. J. 2012;7(2): 54-58